Modelo de gestión administrativo para el “Hostal el Balcón” de la ciudad de Latacunga provincia de Cotopaxi. - Chancusig Toaquiza, Ana Gabriela (2019)
The objective of this investigation project was to design an Administrative Management Model for the "El Balcón" Hostel in the city of Latacunga, Cotopaxi province. Nowadays it is very important to carry out this kind of research that contributes in the management of the hotel companies focused to business growth. The methodology applied was descriptive non-experimental, it had a qualitative approach, for the administrative model determination, the techniques and instruments were used such as, observation sheet, interviews and surveys to the manager, employees and customers of the hostel, that helped to obtain key and true information for the improvement proposal, which is within the line of Administration and Economics for human and social development. The proposal was based on an administrative management model that was guided by the management principles established by the author Henry Fayol: the SWOT situational analysis, planning (mission, vision, values and corporate principles, business objectives and policies), organization (Structure of the organization), direction (manual of functions) and control (Strategies of improvement in the processes of the activities), with the purpose of offering knowledge and solutions with direction to the success in the environment where the problem exists. It will be a great advantage for using this management model in order to improve the service and customer support , in the lodging activity offered by the hostel, with the help of its employees to satisfy its customers, to maintain a favorable economic performance, its recognition and positioning, so in that model is specified how to develop each one of the stages in order that the hostels could be more operational, productive and competitive in the market.